Simulation and Analysis of a Multiphase Adaptive 4-Switch Converter for High-Efficiency Battery Charging Applications - Puneet Kaur (Engineering Research: Perspectives on Recent Advances Vol. 1, 2024)
This paper presents a multiphase 4-switch DC-DC converter optimized for efficient battery charging across variable voltage conditions. Designed for dual-mode operation, it autonomously adapts between buck and boost modes based on the relationship between source and battery voltages, maintaining high efficiency through low-resistance MOSFETs (metal-oxide-semiconductor field-effect transistor) that minimize conduction losses. Employing a multiphase interleaved structure, the converter achieves significant ripple reduction, verified through detailed LT-SPICE (Linear Technology-Simulation Program with Integrated Circuit Emphasis) simulations. Results demonstrate the converter’s performance benefits under diverse charging conditions, making it suitable for high-density battery systems with stringent efficiency and stability requirements.